A letter to my teacher: Interactive written teacher feedback - Keshavarz, Mohammad Hossein; Koseoglu, Meryem Polat (Wiley, 2021)
This study investigated the interactive function of teacher-written feedback. To this end, 10 students from two English toward proficiency (ETP) classes in a private university in North Cyprus were asked to engage in a letter to my teacher (ALMT) activity during the feedback-revision process in the course of their study. Moreover, the think-aloud protocol and a semistructured interview were conducted with the same students and their classroom teachers. The results reveal that the teachers adjusted their feedback according to students' requests in the ALMT, and the students expressed satisfaction with their teachers' feedback. The results further indicate that the students viewed ALMT as their voice in the feedback process, which would lead to their writing improvement, and the teacher participants maintained that ALMT provided a constructive interaction with students and may have increased their self-confidence, motivation, and self-reflection skills.
Keywords: Corrective Feedback; Revision Processes; Students; Error; Improvement